Probing short-range nucleon-nucleon interactions with an electron-ion collider - Miller, Gerald A.; Sievert, Matthew D.; Venugopalan, Raju (Physical review, 2016)
We derive the cross section for exclusive vector meson production in high-energy deeply inelastic scattering off a deuteron target that disintegrates into a proton and a neutron carrying large relative momentum in the final state. This cross section can be expressed in terms of a novel gluon transition generalized parton distribution (T-GPD); the hard scale in the final state makes the T-GPD sensitive to the short-distance nucleon-nucleon interaction. We perform a toy model computation of this process in a perturbative framework and discuss the time scales that allow the separation of initial- and final-state dynamics in the T-GPD. We outline the more general computation based on the factorization suggested by the toy computation: In particular, we discuss the relative role of “pointlike” and “geometric” Fock configurations that control the parton dynamics of short-range nucleon-nucleon scattering. With the aid of exclusive J/ψ production data at the Hadron-Electron Ring Accelerator at DESY, as well as elastic nucleon-nucleon cross sections, we estimate rates for exclusive deuteron photodisintegration at a future Electron-Ion Collider (EIC). Our results, obtained using conservative estimates of EIC integrated luminosities, suggest that center-of-mass energies sNN∼12GeV2 of the neutron-proton subsystem can be accessed. We argue that the high energies of the EIC can address outstanding dynamical questions regarding the short-range quark-gluon structure of nuclear forces by providing clean gluon probes of such “knockout” exclusive reactions in light and heavy nuclei.
Gesehen am 15.05.2020